Space, War, and Deterrence: A Strategy for India. Issue 2 (1st September 2016) - Chandrashekar, S.
ABSTRACT: India must accept and deal with the reality that conflicts and wars in today's world will be driven by the increasing interdependence between conventional, nuclear, and space war. The role of space-based command, control, communications, computers, intelligence, surveillance, and reconnaissance (C4ISR) assets, complemented by other ground- and space-based space situational awareness (SSA) components, is critical for deciding on the new national strategy for waging war and for the deterrence of war. Increasingly, the U.S.-China space dynamic determines the evolution of the global space order. To translate these challenges into an operational capability, India requires, at a minimum, a four-fold increase in capability to launch satellites into various orbits every year. The integration of C4ISR and SSA capabilities into a seamless network that facilitates real-time action is the key organizational and institutional component of the new strategy. More than the technology initiatives, the implementation of this strategy necessitates a clear aspiration on the part of India that it does have an important role to play on the global stage, and that it will carry out the organizational and institutional reforms for defending its national interests and national security.